Kolaviron protects against ethylene glycol monoethyl ether-induced toxicity in boar spermatozoa (2014)
This study investigated the ameliorative effects of kolaviron (a biflavonoid from the seed of Garcinia kola) and vitamin C on ethylene glycol monoethyl ether (EGEE)-induced oxidative damage in boar spermatozoa in vitro. EGEE (1.0 mM) was incubated with boar spermatozoa for 3 h with or without either kolaviron (50 and 100 lM) or vitamin C (1.0 mM). Spermatozoa parameters were determined hourly during the incubation period, whereas aminotransferases and alkaline phosphatase activities and oxidative stress indices were assessed after the incubation period. Results showed a time-dependent decline in spermatozoa motility and viability with significant elevation in total abnormalities in EGEE-treated spermatozoa. Exposure to EGEE resulted in significant increase in aminotransferases, alkaline phosphatase and superoxide dismutase (SOD) activities, whereas it markedly decreased glutathione (GSH) level, catalase (CAT) and glutathione S-transferase (GST) activities with concomitant increase in hydrogen peroxide (H2O2) and malondialdehyde (MDA) levels. Pre-treatment of spermatozoa with kolaviron or vitamin C significantly decreased H2O2 and MDA levels, improved spermatozoa characteristics and ameliorated oxidative damage in EGEE-treated spermatozoa. Taken together, EGEE exhibited its spermatotoxicity via induction of oxidative stress. The protective effects by kolaviron and vitamin C against EGEE-induced oxidative damage may be due to their intrinsic antioxidative potentials.